A Medium-Scale Distributed System for Computer Science Research: Infrastructure for the Long Term - Bal, Henri; Epema, Dick; de Laat, Cees; van Nieuwpoort, Rob; Romein, John; Seinstra, Frank; Snoek, Cees; Wijshoff, Harry (Computer (Long Beach, Calif.), 2016)
The Dutch Advanced School for Computing and Imaging has built five generations of a 200-node distributed system over nearly two decades while remaining aligned with the shifting computer science research agenda. The system has supported years of award-winning research, underlining the benefits of investing in a smaller-scale, tailored design.